2012
DOI: 10.1111/j.1468-2427.2012.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

When an NGO Takes on Public Participation: Preparing a Plan for a Neighborhood in East Jerusalem

Abstract: It is often non-governmental organizations (NGOs) that promote empowered participation processes, and assume active roles in leading them. However, the ability of NGOs to take on such processes is under-theorized. In many cases empowered participation involving NGOs takes place without political support from above (or with limited or conditional support). Our goal in this article is to use a case study of participatory planning in East Jerusalem to theorize processes of empowerment in an oppositional political… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…This is especially true when formal government promotion of community participation, exhibited by the existence of these contracts and national policies, does not translate to ground reality, exhibited by weak government capacity to engage with communities. Nongovernmental organizations must navigate power relations that strain community trust and can lead to distressing interactions with frustrated community members . The intervention ended with many communities unconvinced about the VHSNCs' utility.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true when formal government promotion of community participation, exhibited by the existence of these contracts and national policies, does not translate to ground reality, exhibited by weak government capacity to engage with communities. Nongovernmental organizations must navigate power relations that strain community trust and can lead to distressing interactions with frustrated community members . The intervention ended with many communities unconvinced about the VHSNCs' utility.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Bimkom made efforts to improve the well‐being of the communities by means of empowerment, that is, proactive interventions designed to raise civic activism, improve capabilities, and increase the responsibility of the citizens toward the community (Bacqué & Biewener, , p. 2208). An example of applying this strategy can be seen in the “Issawiyah project” (Cohen‐Blankshtain, Ron, & Perez, ). Issawiyah is an Arab neighborhood in East Jerusalem, with the population suffering from inequality and lack of opportunity .…”
Section: Bimkom: General Characteristics and Strategymentioning
confidence: 99%
“…To change this situation, in 2003–2012, Bimkom initiated several actions, including the preparation of an alternative master plan, intended for submission to the official planning authority of the Jerusalem Municipality, and the establishment of a social team, with the aim of informing the residents about the planning process and organizing discussions on the neighborhood vision. Cohen‐Blankshtain et al () revealed an underlying objective behind the establishment of the social team: empowering participation. The latter refers to the idea that no matter what are the practical results, there is much value in learning skills and internalizing ideas that help community members recognize their ability to make change and develop a new notion of “we.”…”
Section: Bimkom: General Characteristics and Strategymentioning
confidence: 99%
See 2 more Smart Citations